1990
DOI: 10.1136/ard.49.9.668
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and reactivity of the sulphydryl group population on the membrane of intact erythrocytes in patients with rheumatoid arthritis.

Abstract: The sulphydryl population on erythrocyte membrane is shown to vary as a function of the nutritional status of the cell. When an assay based on reaction with Eliman's reagent and controlled conditions were used the mean values (SEM) for the sulphydryl population on the membranes of normal erythrocytes incubated overnight in the presence and absence of glucose were found to be 3-29 (0.27) and 2 56 (0.25) million sulphydryl functions per cell respectively. Under identical conditions rheumatoid erythrocytes incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 26 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…It has been known for more than two decades that plasma or red blood cells taken from RA patients have significantly reduced free sulfhydryl levels [106,107] or elevated lipid oxidation by-products such as MDA [43]. For example, Miesel et al [16] reported that the plasma free sulfhydryl content was reduced by 45-75% in serum from RA patients versus healthy controls, whereas levels of XO were increased up to 50-fold.…”
Section: Markers Of Oxidant Stress In Ra Patientsmentioning
confidence: 96%
“…It has been known for more than two decades that plasma or red blood cells taken from RA patients have significantly reduced free sulfhydryl levels [106,107] or elevated lipid oxidation by-products such as MDA [43]. For example, Miesel et al [16] reported that the plasma free sulfhydryl content was reduced by 45-75% in serum from RA patients versus healthy controls, whereas levels of XO were increased up to 50-fold.…”
Section: Markers Of Oxidant Stress In Ra Patientsmentioning
confidence: 96%